Joint pain and joint hypermobility in inflammatory bowel disease. (13th March 2011) - Fikree, A; Aziz, Q; Aktar, R; Hartley, F; Denning, C; Grahame, R; Rampton, D
Abstract : Introduction: Joint hypermobility (JHM) refers to the hyperextensibility of joints and is common, with a prevalence of 5–17%.1 It is associated with joint pain but unlike conventional arthropathies, radiological and inflammatory marker abnormalities are absent. JHM tends to be under-diagnosed, even by rheumatologists. Joint pain is common in inflammatory bowel disease (IBD) and is often attributed to seronegative arthropathy. A recent small study suggested that JHM was more common in patients with CD than in UC and healthy controls, and may account for joint pain in these patients.2 Methods: We aimed to assess whether: (1) JHM is more common in patients with IBD than in healthy controls. (2) Joint pain is more common in patients with JHM than without. (3) Patients with JHM and joint pain are misdiagnosed as having arthropathies. In a dual-centre prospective observational study in secondary care, 348 follow-up patients (51% female; age range 16–90) attending IBD clinics were asked to complete a validated 5-point JHM questionnaire, and answer questions related to joint pain, previous diagnoses of arthritis and analgesic use. Patients who scored positive on ≥2 hypermobility questions were considered hypermobile. For patients reporting 'arthritis', medical records were checked for a rheumatology diagnosis.250 healthy volunteers with no joint pain served as controls. Results: 19% patients were hypermobile. There was no difference in the prevalence of JHM in CD (18%) compared to UC (21%) or healthy controls (18%), p=0.49. 56% IBD patients reported joint pain: more patients with JHM (69%) than without (53%, p=0.03) complained of joint pain, but they were less likely to use analgesia (23%) than those without JHM (36%, p<0.05). Of 176 patients reporting joint pain, only 21% had a rheumatological diagnosis of arthropathy and this was similar whether they had (24%) or did not have JHM (20%, p=0.61). Only one patient with joint pain (0.1%) had been diagnosed with hypermobility. Conclusion: The prevalence of JHM is not increased in patients with IBD, whether CD or UC. More patients with than without JHM have joint pains but the two groups are equally likely to be diagnosed with arthropathy. Only 1 patient had been diagnosed with hypermobility. Hypermobility seems to be under-diagnosed in patients referred from IBD to rheumatology clinics for assessment of joint pain and should be considered when patients do not clearly satisfy criteria for other arthropathies to ensure they are treated appropriately.